2021
DOI: 10.51153/mf.v16i1.480
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Customer Loyalty: Exploring the Role of Satisfaction and Corporate Image in the Banking Industry

Abstract: This study aims to determine the impact of corporate social responsibility on customerloyalty and satisfaction with the mediating effect of customer satisfaction and the moderatingeffect of corporate image in Pakistan’s banking sector. The study collected 302 responsesfrom the target population. We used a self-administered questionnaire for collecting thedata of banking customers in Pakistan by employing the convenience sampling technique.The study has used the PLS-SEM technique for statistical analysis. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…As a result, academics recognise perceived value as a significant factor in today's economy (Ishaq, 2012) and a source of competitive advantage (Nikhashemi et al, 2016). The researchers investigated the relationship between CPV and loyalty (Piyathasanan et al, 2015;Lam, 2016;Shi et al, 2017). Despite this, the literature on the impact of CSR on perceived value and perceived value as a mediator between CSR and consumer loyalty is lacking.…”
Section: Mediating Effects Of Customer Perceived Valuementioning
confidence: 99%
See 2 more Smart Citations
“…As a result, academics recognise perceived value as a significant factor in today's economy (Ishaq, 2012) and a source of competitive advantage (Nikhashemi et al, 2016). The researchers investigated the relationship between CPV and loyalty (Piyathasanan et al, 2015;Lam, 2016;Shi et al, 2017). Despite this, the literature on the impact of CSR on perceived value and perceived value as a mediator between CSR and consumer loyalty is lacking.…”
Section: Mediating Effects Of Customer Perceived Valuementioning
confidence: 99%
“…Therefore, researchers and industrialists have shown a substantial interest in CSR (Pratihari and Uzma, 2018; Pirsch et al , 2007; He and Li, 2011; Nejati and Ghasemi, 2012). In the early days, the firm’s goals and objectives focused on sales volume, revenues and market share; however, it was also directed to attain the organisation’s social contributions (Samra and Wady, 2017). CSR is simply defined as “the responsibility of the entrepreneur for his or her influences on society” (Commission of the European Communities, 2011).…”
Section: Review Of Related Literature and Development Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the stakeholders' positive attitudes towards a business's social activities may support the firm's competitive advantage and attract a quality workforce [21] CSR initiatives directed towards employees, customers and society have been tested and found to be positively and significantly related to firm performance [22,23]. The study conducted by [24] indicated that secondary stakeholders, including governments, the media, communities and non-governmental organisations (NGOs), have the most significant influence on firms' strategies [25] mentioned that studies in the banking sector suggested that reporting CSR activities can influence stakeholders' perceptions of a company's performance and increase its profitability [23]. Studies examining stakeholders' perceptions and attitudes towards CSR in Lebanon are limited; only a few have attempted to study the perceptions and behaviours of stakeholders towards CSR.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%